Low-income youth and long-term school permanence: the senses built up by Prouni scholarship holders in Belo Horizonte (MG) - do Carmo Sousa, Maria; Ignez Costa Moreira, Maria (Revista Pesquisas e Práticas Psicossociais, 2017)
This article is derived from a doctoral research carried out in Belo Horizonte (MG), aiming at learning and understanding the senses low-income youths, who are Prouni (University for All Program) scholarship holders, set up concerning long-term school permanence. The qualitative study is anchored in the theoretical-methodological principles of Socio-Historical Psychology, which emphasizes the constitution of the subject in the socio-historical context, in addition to the subjects’ activity as potential changers of their own context. In order to understand low-income youths’ unique experience of long-term school permanence, we present the notion of youth as a plural category, as well as the Prounischolarship holders’ life contexts, and the senses they develop based on their own experience as university students, which we collected using semi-structured interviews. Keywords: Prouni; Low-income youth; School permanence; Higher education; Socio-Historical Psychology.